The role of structural parameters on efficiency and transparency of semi-transparent non-fullerene organic solar cell - Elmira Annabi Milani; Mina Piralaee; Sohrab Ahmadi; Asghar Asgari (Scientific Reports, 2022)
Abstract Semitransparent organic solar cells have become attractive recently because of their photon harvesting in the near-infrared and ultraviolet range and passing in the visible light region. Semitransparent organic solar cells with ITO/ZnO/PBDB-T:ITIC/MoO3/Ag/MoO3 structure have been studied in this work and the effects of PBDB-T:ITIC active layer thicknesses and the transparent top electrode, MoO3/Ag/MoO3, thickness on the solar cell performance such as I-V characteristics, the power conversion efficiency, the average visible transmittance, and the color coordinates in the CIE color space are investigated. The drift–diffusion model, including the density of exactions, and their displacement is used to model the devices. The model is examined with experimentally reported devices, where there is a very good agreement between them, then is applied to the new structures. The obtained results show that the average visible transmittance of more than 45% is achievable for these structures with reasonable power conversion efficiency.